Monitoring device of ice formation in evaporator surface of refrigeration systems - Graça, Marcos (2019)
In order to achieve lower temperatures than ambient air, whether for food cold storage purposes or thermal comfort, the evaporator coils generally operate at lower temperatures than the freezing point of water. The ice formed on the evaporator surface is disadvantageous for the energy efficiency and performance of the refrigeration system. Thus, its removal is crucial to restore the desired operating conditions. This paper studies the feasibility of using a simple and low cost device for monitoring the ice formation on the surface of evaporators. The concept of the developed device is based on variation imposed by the ice formation on the electrical resistance measured between electrodes. Through a detailed analysis of results, the electronic circuit capable of automating the entire process has been designed and projected on a printed circuit board. The results show that both the circuit configuration and the concept have potential to be used as ice formation monitoring devices. Some adjustments have to be included in the device to achieve a widespread application level.